Music and Academic Performance: Impact of Listening to Music of Filipino Millennials - Maynes-Blanco, Desserie T.; Nartea, Mecmack A. (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to identify the impact of listening to music on the student’s academic performance at Polytechnic University of the Philippines. This quantitative study involved 395 students who voluntarily participated and answered the survey questionnaire. In this research, Chi-square and Pearson Correlation were utilized as statistical tools.The study reveals that Filipino students acquired good grades but cannot be directly attributed to music alone because not all students listen to music. It is also found out that the students spend their time the most in listeninat=3g to music; loud music is the most commonly heard but they preferred Pop music. Results also revealed no significant relationship between year level and impact of listening to music to the academic performance, but significant to college and time length of listening. Type of music and GWA also were insignificant to the impact of listening to music.